Human papillomavirus type 38 E6 and E7 act as tumour promoters during chemically induced skin carcinogenesis - Viarisio, Daniele; Müller-Decker, Karin; Aengeneyndt, Birgit; Flechtenmacher, Christa; Gissmann, Lutz; Tommasino, Massimo (Journal of general virology, 2013)
Many findings support a possible involvement of a subgroup of human papillomaviruses (HPVs), called cutaneous beta HPV types, in the development of non-melanoma skin cancer. The skin of transgenic (Tg) mice expressing viral oncoproteins E6 and E7 from different cutaneous beta HPV types, including HPV38, showed an increased susceptibility to UV-induced and/or chemically induced skin carcinogenesis compared with wild-type animals. In this study, we show that beta HPV38 E6 and E7 oncoproteins act as promoter and progression factors in multi-stage skin carcinogenesis, strongly cooperating with the initiator and DNA damage agent 7,12-dimethylbenz[a]anthracene. In contrast, exposure of HPV38 E6/E7 Tg mice to the promoter 12-O-tetradecanoylphorbol-13-acetate did not significantly result in the development of skin lesions. These findings further support the role of beta HPV types in skin carcinogenesis, providing additional insight into their precise contribution to the multi-step process.